Antibacterial PET cup material and preparation method thereof
By combining maleic anhydride grafting and electron beam radiation co-modification of PET with thermally activated carbon-based nano-antibacterial agents, the problem of easy bacterial growth in PET materials was solved, achieving efficient, stable antibacterial properties and durability.
Patent Information
- Application Number
- CN202511161942.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-25
AI Technical Summary
Existing PET materials are prone to bacterial growth during use, leading to health problems. Furthermore, traditional metal ion modification methods have unstable antibacterial durability and the risk of heavy metal pollution.
PET was co-modified by maleic anhydride grafting and electron beam radiation, and then combined with thermally activated carbon-based nano-antibacterial agents and dispersants. Antibacterial PET materials were prepared by thermal activation treatment to form carbon dot/chitosan complexes, thereby improving antibacterial properties.
The prepared antibacterial PET material has good antibacterial effect and relatively long-lasting and stable performance, while also having high tensile strength, which improves the durability of the water cup.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of antibacterial plastic cup materials, in particular to an antibacterial PET cup material and a preparation method thereof. BACKGROUND
[0002] Polyethylene terephthalate (PET) has good mechanical properties, transparency, chemical stability and processing performance, and is non-toxic, odorless, lightweight, not easy to break, and low in cost, and is widely used in cup manufacturing.
[0003] PET material itself does not have antibacterial properties, and bacteria can easily breed during use, causing health problems. In order to increase the antibacterial properties of PET material, the prior art can use methods such as grafting metal ions to modify PET material.
[0004] For example, CN106832820B discloses a degradable disposable composite plastic water cup and a preparation method thereof, which is prepared from the following raw materials: 45-55% of PET or modified PET, 25-35% of polybutylene succinate, 5-15% of starch, 1-3% of photodegradation accelerator, 2-6% of glass fiber, 1-3% of thermal stabilizer, and 1-3% of lubricant. The modified PET is modified by metal ions, and the metal ions are uniformly dispersed between the plastic molecules to achieve antibacterial effect.
[0005] However, metal ions may dissolve during use, which not only affects the durability of antibacterial properties, but also causes heavy metal pollution, endangering human health and environmental safety, in addition, the overall antibacterial properties of the material are unstable, and the antibacterial properties of the water cup still need to be further improved.
[0006] Therefore, the present application designs an antibacterial PET cup material and a preparation method thereof to solve the above problems. SUMMARY
[0007] In view of the above shortcomings of the prior art, the present application provides an antibacterial PET cup material and a preparation method thereof.
[0008] To achieve the above purpose, the present application realizes the following technical scheme:
[0009] An antibacterial PET cup material, comprising the following raw materials by weight: maleic anhydride grafted and electron beam radiation co-modified PET 85.6-92.7 parts, heat-activated carbon-based nano-antibacterial agent 6.3-12.3 parts, dispersing agent 1.5-2.3 parts, and antioxidant 0.5-1.3 parts.
[0010] The maleic anhydride grafted and electron beam radiation co-modified PET is obtained by grafting and modifying PET with maleic anhydride and then modifying it with electron beam radiation.
[0011] The preparation method of the heat-activated carbon-based nano-antibacterial agent is as follows: first, APTES and citric acid are used to synthesize carbon dots by a hydrothermal method, the carbon dots are compounded with chitosan after charge adjustment, and the heat-activated carbon-based nano-antibacterial agent is prepared after heat activation treatment.
[0012] Further, the preparation method of the PET modified by maleic anhydride and electron beam radiation is as follows:
[0013] 1) 85-100 parts of PET, 3-8 parts of maleic anhydride, and 0.1-0.2 parts of initiator are weighed and blended and extruded at 250-280 ℃ to obtain maleic anhydride grafted modified PET;
[0014] 2) The maleic anhydride grafted modified PET is placed in an electron beam radiation device under a nitrogen protective atmosphere, the radiation dose is 85-125 kGy, the radiation energy is 5-10 MeV, and the scanning speed is 1-3 m / min.
[0015] Further, the initiator is dicumyl peroxide DCP.
[0016] Further, the preparation method of the heat-activated carbon-based nano-antibacterial agent is as follows:
[0017] (1) APTES and citric acid are added to deionized water, stirred uniformly, and then the pH of the solution is adjusted to 7-8;
[0018] (2) The mixed solution is placed in a hydrothermal kettle and reacted at 185-198 ℃ for 5-8 h, and then cooled;
[0019] (3) The reaction product is filtered using a filter membrane to remove large particle impurities, and then purified by dialysis bag to obtain a carbon dot solution;
[0020] (4) HCl solution is added dropwise to the carbon dot solution, and the pH is adjusted to 3-4 under stirring;
[0021] (5) Chitosan is weighed and added to glacial acetic acid solution to prepare a 0.5-2% chitosan acid solution; the carbon dot solution is slowly added to the chitosan solution for stirring reaction, and the precipitate is collected after centrifugation to obtain a carbon dot / chitosan composite;
[0022] (6) Heat activation treatment: the carbon dot / chitosan composite is heated to 135-158 ℃ at a heating rate of 5-10 ℃ / min under a nitrogen protective atmosphere, and heat-activated for 1-2 h, and finally ground to obtain a heat-activated carbon-based nano-antibacterial agent.
[0023] Further, step (1) is specifically: 0.5-1.5 mL APTES and 2-5 g citric acid are added to 85-105 mL deionized water, stirred for 20-30 minutes, and the solution pH is adjusted to 7-8.
[0024] Further, step (3) is specifically: the reaction product is filtered using a 0.22 μm filter membrane to remove large particulate impurities, and then dialyzed using a dialysis bag with a molecular weight cut-off of 1000-3000 Da for 24-38 h to obtain a carbon dot solution.
[0025] Further, in step (5), the volume ratio of the carbon dot solution to the chitosan solution is 1:8-15.
[0026] Further, in step (5), the carbon dot solution is slowly added to the chitosan solution, stirred at 35-45 ℃ for 2-4 h, centrifuged at a speed of 8000-10000 r / min for 5-10 min, and the precipitate is collected to obtain a carbon dot / chitosan composite.
[0027] Further, the antioxidant is antioxidant 1010.
[0028] In order to better achieve the purpose of the present application, the present application also provides a preparation method of an antibacterial PET cup material, comprising the following steps:
[0029] (1) First, the maleic anhydride grafted and electron beam radiation co-modified PET and the antioxidant are added to a high-speed mixer and mixed at a low speed at 60-80 ℃ for 5-8 minutes;
[0030] (2) Then, the heat-activated carbon-based nano-antibacterial agent and the dispersing agent are added and mixed at a high speed for 10-15 minutes;
[0031] (3) Then, the mixture is heated and melt-extruded, the extrusion temperature is 250-280 ℃, and the extrudate is cooled and pelletized to obtain an antibacterial PET composite master batch, which is ready for use.
[0032] Compared with the prior art, the antibacterial PET material prepared by the present application has good antibacterial effect and relatively durable and stable antibacterial performance, and has high tensile strength, which is beneficial to improve the durability of the water cup. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the embodiments of the present application will be described clearly and completely below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0034] Example 1: A method for preparing an antibacterial PET cup, comprising the following steps:
[0035] Step one, preparation of maleic anhydride grafted, electron beam radiation co-modified PET
[0036] 1) Take 85 parts of PET, 8 parts of maleic anhydride (MAH), and 0.1 parts of initiator (dicumyl peroxide DCP), and blend and extrude at 250-280 ℃ to obtain maleic anhydride grafted modified PET;
[0037] 2) Under the protection of nitrogen atmosphere, put the maleic anhydride grafted modified PET into the electron beam radiation device, the radiation dose is 85 kGy, the radiation energy is 10 MeV, and the scanning speed is 1 m / min.
[0038] Step two, preparation of heat-activated carbon-based nano-antibacterial agent
[0039] (1) Add 0.5 mL of APTES and 5 g of citric acid to 85 mL of deionized water, and magnetically stir for 30 minutes, adjust the solution pH to 7;
[0040] (2) Put the mixed solution in a hydrothermal kettle and react at 185 ℃ for 8 h, and cool;
[0041] (3) The reaction product is filtered to remove large particle impurities using a 0.22 μm filter membrane, and then dialyzed for 38 h using a dialysis bag with a molecular weight cutoff of 1000-3000 Da to obtain a carbon dot solution;
[0042] (4) Add 0.5 mol / L of HCl solution dropwise to the carbon dot solution, and adjust the pH to 3 under stirring to protonate the amino groups (-NH2) on the surface of the carbon dots to ammonium groups (-NH3⁺);
[0043] (5) Take 0.5 g of chitosan, add 100 mL of 1% (v / v) glacial acetic acid solution, and prepare a 2% (wt) chitosan acidic solution; slowly add the carbon dot solution to the chitosan solution, and the volume ratio of the carbon dot solution to the chitosan solution is 1:8, stir at 45 ℃ for 2 h, centrifuge at 10000 r / min for 5 min, collect the precipitate, and obtain a carbon dot / chitosan composite;
[0044] (6) Heat activation treatment: heat the carbon dot / chitosan composite to 158 ℃ at a heating rate of 5 ℃ / min under a nitrogen atmosphere, and heat for 1 h for heat activation treatment, and finally grind to obtain a heat-activated carbon-based nano-antibacterial agent.
[0045] Step three, according to the weight parts of the following raw materials: maleic anhydride graft, electron beam radiation co-modified PET 85.6 parts, heat-activated carbon-based nano-antibacterial agent 12.3 parts, dispersant (magnesium stearate) 2.3 parts, antioxidant 1010 1.3 parts; first, maleic anhydride graft, electron beam radiation co-modified PET and antioxidant 1010 are added to a high-speed mixer, mixed at 60°C for 5 minutes at low speed (800 r / min), then heat-activated carbon-based nano-antibacterial agent and dispersant are added, mixed at high speed (1500 r / min) for 10 minutes, then melt extruded by heating, the extrusion temperature is 250-280 ℃, the extrudate is cooled, granulated, to obtain antibacterial PET composite master batch, ready for use.
[0046] Step four, using antibacterial PET composite master batch for injection molding, to obtain antibacterial PET cup.
[0047] Example 2: A method for preparing an antibacterial PET cup, comprising the following steps:
[0048] Step one, preparing maleic anhydride graft, electron beam radiation co-modified PET
[0049] 1) Take PET 100 parts, maleic anhydride (MAH) 3 parts, initiator (dicumyl peroxide DCP) 0.2 parts, blend and extrude at 250-280 ℃ to obtain maleic anhydride grafted modified PET;
[0050] 2) Under the protection of nitrogen atmosphere, the maleic anhydride grafted modified PET is placed in an electron beam radiation device, the radiation dose is 125 kGy, the radiation energy is 5 MeV, and the scanning speed is 3 m / min.
[0051] Step two, preparing heat-activated carbon-based nano-antibacterial agent
[0052] (1) 1.5 mL APTES and 2 g citric acid are added to 105 mL deionized water, magnetically stirred for 20 minutes, and the solution pH is adjusted to 8;
[0053] (2) The mixed solution is placed in a hydrothermal kettle and reacted at 198 ℃ for 5 h, and then cooled;
[0054] (3) The reaction product is filtered using a 0.22 μm filter membrane to remove large particle impurities, and then dialyzed for 24 h using a dialysis bag with a molecular weight cutoff of 1000-3000 Da to obtain a carbon dot solution;
[0055] (4) 0.5 mol / L HCl solution is added dropwise to the carbon dot solution, and the pH is adjusted to 4 under stirring to protonate the amino groups (-NH2) on the surface of the carbon dots to ammonium groups (-NH3⁺);
[0056] (5) Take 2 g of chitosan, add 100 mL of 1% (v / v) glacial acetic acid solution to prepare a 0.5% (wt) chitosan acidic solution; slowly add the carbon dot solution to the chitosan solution, the volume ratio of the carbon dot solution to the chitosan solution is 1:15, stir at 35 ℃ for 4 h, centrifuge at 8000 r / min for 10 min, collect the precipitate, and obtain the carbon dot / chitosan composite;
[0057] (6) Thermal activation treatment: heat the carbon dot / chitosan composite to 135 ℃ at a heating rate of 10 ℃ / min under a nitrogen protective atmosphere, and heat for 2 h for thermal activation treatment, and finally grind to obtain a thermal activated carbon-based nanometer antibacterial agent.
[0058] Step three, according to the weight fraction, the following raw materials are taken: maleic anhydride grafted, electron beam radiation co-modified PET 92.7 parts, thermal activated carbon-based nanometer antibacterial agent 6.3 parts, dispersing agent (magnesium stearate) 1.5 parts, antioxidant 1010 0.5 parts; first, the maleic anhydride grafted, electron beam radiation co-modified PET and antioxidant 1010 are added to a high-speed mixer, mixed at 80 ℃ at low speed (500 r / min) for 8 minutes, then the thermal activated carbon-based nanometer antibacterial agent and the dispersing agent are added, and mixed at high speed (1200 r / min) for 15 minutes, and then extruded by heating and melting, the extrusion temperature is 250-280 ℃, the extrudate is cooled, granulated, to obtain an antibacterial PET composite master batch, ready for use.
[0059] Step four, using the antibacterial PET composite master batch for injection molding to obtain an antibacterial PET cup.
[0060] Example 3: A method for preparing an antibacterial PET cup, comprising the following steps:
[0061] Step one, preparing maleic anhydride grafted, electron beam radiation co-modified PET
[0062] 1) Take PET 96 parts, maleic anhydride (MAH) 5.5 parts, and initiator (dicumyl peroxide DCP) 0.12 parts, and extrude at 250-280 ℃ to obtain maleic anhydride grafted modified PET;
[0063] 2) Under a nitrogen protective atmosphere, the maleic anhydride grafted modified PET is placed into an electron beam radiation device, the radiation dose is 108 kGy, the radiation energy is 6 MeV, and the scanning speed is 2 m / min.
[0064] Step two, preparing a thermal activated carbon-based nanometer antibacterial agent
[0065] (1) Add 1.1 mL of APTES and 3.2 g of citric acid to 95 mL of deionized water, and magnetically stir for 24 minutes, and adjust the solution pH to 7.5;
[0066] (2) The mixed solution was placed in a hydrothermal kettle and reacted at 190°C for 6.5 h, and then cooled;
[0067] (3) The reaction product was filtered using a 0.22 μm filter membrane to remove large particulate impurities, and then dialyzed using a dialysis bag with a molecular weight cutoff of 1000-3000 Da for 30 h to obtain a carbon dot solution;
[0068] (4) 0.5 mol / L HCl solution was added dropwise to the carbon dot solution, and the pH was adjusted to 3.5 under stirring to protonate the amino groups (-NH2) on the surface of the carbon dots to ammonium groups (-NH3⁺);
[0069] (5) 1.2 g of chitosan was weighed and added to 100 mL of 1% (v / v) glacial acetic acid solution to prepare a 1% (wt) chitosan acidic solution; the carbon dot solution was slowly added to the chitosan solution, and the volume ratio of the carbon dot solution to the chitosan solution was 1:10, and the mixture was stirred at 40°C for 3 h and centrifuged at 9000 r / min for 7 min, and the precipitate was collected to obtain a carbon dot / chitosan composite;
[0070] (6) Thermal activation treatment: the carbon dot / chitosan composite was heated to 145°C at a heating rate of 7.5°C / min under a nitrogen protective atmosphere, and then heat-activated for 1.5 h, and finally ground to obtain a heat-activated carbon-based nanometer antibacterial agent.
[0071] Step three, the following raw materials were weighed according to the weight fraction: maleic anhydride grafted, electron beam radiation co-modified PET 88.5 parts, heat-activated carbon-based nanometer antibacterial agent 8.5 parts, dispersing agent (magnesium stearate) 2.0 parts, antioxidant 1010 0.8 parts; first, the maleic anhydride grafted, electron beam radiation co-modified PET and antioxidant 1010 were added to a high-speed mixer and mixed at a low speed (600 r / min) at 75°C for 6 minutes, then the heat-activated carbon-based nanometer antibacterial agent and the dispersing agent were added and mixed at a high speed (1350 r / min) for 12 minutes, and then extruded by heating and melting, the extrudate was cooled and pelletized to obtain an antibacterial PET composite master batch, which was ready for use.
[0072] Step four, the antibacterial PET composite master batch was used for injection molding to obtain an antibacterial PET cup.
[0073] Comparative Example 1: Different from Example 3, the maleic anhydride grafted, electron beam radiation co-modified PET is replaced by maleic anhydride grafted modified PET. The preparation method of the maleic anhydride grafted modified PET is as follows: taking PET 96 parts, maleic anhydride (MAH) 5.5 parts, initiator (dicumyl peroxide DCP) 0.12 parts, blending and extruding at 250-280 ℃ to obtain maleic anhydride grafted modified PET.
[0074] Comparative Example 2: Different from Example 3, the carbon-based nano-antibacterial agent is not subjected to charge adjustment during the preparation process. The preparation method of the heat-activated carbon-based nano-antibacterial agent is as follows:
[0075] (1) 1.1 mL of APTES and 3.2 g of citric acid were added to 95 mL of deionized water, and the solution was magnetically stirred for 24 minutes to adjust the pH to 7.5;
[0076] (2) The mixed solution was placed in a hydrothermal kettle and reacted at 190 ℃ for 6.5 h, and then cooled;
[0077] (3) The reaction product was filtered to remove large particle impurities using a 0.22 μm filter membrane, and then dialyzed for 30 h using a dialysis bag with a molecular weight cut-off of 1000-3000 Da to obtain a carbon dot solution;
[0078] (4) 1.2 g of chitosan was weighed and added to 100 mL of 1% (v / v) glacial acetic acid solution to prepare a 1% (wt) chitosan acidic solution; the carbon dot solution was slowly added to the chitosan solution, and the volume ratio of the carbon dot solution to the chitosan solution was 1:10, and the mixture was stirred at 40 ℃ for 3 h, and then centrifuged at 9000 r / min for 7 min to collect the precipitate to obtain a carbon dot / chitosan composite;
[0079] (5) Heat activation treatment: the carbon dot / chitosan composite was heated to 145 ℃ at a heating rate of 7.5 ℃ / min under a nitrogen protective atmosphere, and heat-activated for 1.5 h, and then ground to obtain a heat-activated carbon-based nano-antibacterial agent.
[0080] Comparative Example 3: Different from Example 3, the carbon-based nano-antibacterial agent is not subjected to heat activation treatment after the carbon dots are compounded. The preparation method of the carbon-based nano-antibacterial agent is as follows:
[0081] (1) 1.1 mL of APTES and 3.2 g of citric acid were added to 95 mL of deionized water, and the solution was magnetically stirred for 24 minutes to adjust the pH to 7.5;
[0082] (2) The mixed solution was placed in a hydrothermal kettle and reacted at 190 ℃ for 6.5 h, and then cooled;
[0083] (3) The reaction product was filtered using a 0.22 μm filter to remove large particle impurities, and then dialyzed using a dialysis bag with a molecular weight cutoff of 1000-3000 Da for 30 h to obtain a carbon dot solution;
[0084] (4) 0.5 mol / L HCl solution was added dropwise to the carbon dot solution, and the pH was adjusted to 3.5 under stirring to protonate the amino groups (-NH2) on the surface of the carbon dots into ammonium groups (-NH3⁺);
[0085] (5) 1.2 g of chitosan was weighed and added to 100 mL of 1% (v / v) glacial acetic acid solution to prepare a 1% (wt) chitosan acidic solution; the carbon dot solution was slowly added to the chitosan solution, and the volume ratio of the carbon dot solution to the chitosan solution was 1:10, and the mixture was stirred at 40 ℃ for 3 h and centrifuged at 9000 r / min for 7 min. The precipitate was collected to obtain a carbon dot / chitosan composite, and finally the carbon-based nanometer antibacterial agent was obtained after grinding.
[0086] Comparative Example 4: Different from Example 3, during the preparation of the carbon-based nanometer antibacterial agent, the carbon dots were not subjected to charge adjustment, and the carbon dots were not subjected to heat activation treatment after being compounded with chitosan.
[0087] The preparation method of the carbon-based nanometer antibacterial agent is as follows:
[0088] (1) 1.1 mL of APTES and 3.2 g of citric acid were added to 95 mL of deionized water, and the solution was magnetically stirred for 24 minutes to adjust the pH to 7.5;
[0089] (2) The mixture was placed in a hydrothermal kettle and reacted at 190 ℃ for 6.5 h, and then cooled;
[0090] (3) The reaction product was filtered using a 0.22 μm filter to remove large particle impurities, and then dialyzed using a dialysis bag with a molecular weight cutoff of 1000-3000 Da for 30 h to obtain a carbon dot solution;
[0091] (4) 1.2 g of chitosan was weighed and added to 100 mL of 1% (v / v) glacial acetic acid solution to prepare a 1% (wt) chitosan acidic solution; the carbon dot solution was slowly added to the chitosan solution, and the volume ratio of the carbon dot solution to the chitosan solution was 1:10, and the mixture was stirred at 40 ℃ for 3 h and centrifuged at 9000 r / min for 7 min. The precipitate was collected to obtain a carbon dot / chitosan composite, and finally the carbon-based nanometer antibacterial agent was obtained after grinding.
[0092] Experimental Example: The surface antibacterial performance (GB / T31402-2023) and tensile strength (GB / T 1040.1-2018) of the antibacterial PET materials prepared in Examples 1-3 and Comparative Examples 1-3 were detected.
[0093] Table 1
[0094] Test item Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Antibacterial rate against E. coli, % 99.8 99.7 100 99.4 96.1 89.4 87.9 Antibacterial rate against S. aureus, % 99.6 99.4 99.8 99.3 94.0 86.8 84.3 Antibacterial rate against E. coli after 30 days of immersion, % 99.4 99.2 99.7 86.7 78.9 66.7 60.1 Antibacterial rate against S. aureus after 30 days of immersion, % 99.3 99.0 99.4 83.5 70.6 63.2 57.4 Tensile strength, MPa 47.6 48.3 47.9 43.7 47.6 48.0 47.4
[0095] As can be seen from Table 1, the antibacterial PET material prepared in Examples 1-3 has good antibacterial effect and relatively durable and stable antibacterial performance, and high tensile strength, thereby improving the durability of the water cup.
[0096] As can be seen from Examples 3 and Comparative Example 1, if the PET modified by grafting maleic anhydride and electron beam radiation is replaced by PET modified by grafting maleic anhydride, the crosslinking degree of the PET is reduced, the tensile strength is reduced, and the compatibility with the antibacterial agent is poor, resulting in uneven dispersion of the antibacterial agent, a decrease in the initial antibacterial rate, and a significant decrease in the antibacterial rate after immersion.
[0097] As can be seen from Examples 3 and Comparative Example 2, if the carbon dots are not subjected to charge adjustment during the preparation of the heat-activated carbon-based nano-antibacterial agent, the amino groups on the surface of the carbon dots are not protonated, the positive charge density is low, the electrostatic interaction with bacteria and chitosan is weakened, the dispersibility of the antibacterial agent is reduced, and the initial antibacterial rate is reduced; the antibacterial components are prone to migrate and be lost after immersion, and the antibacterial rate is significantly reduced.
[0098] As can be seen from Examples 3 and Comparative Example 3, if the carbon dots are not subjected to heat activation after being compounded with chitosan during the preparation of the carbon-based nano-antibacterial agent, the initial antibacterial rate is low, and the antibacterial components are prone to migrate and be lost in large quantities after immersion, and the antibacterial rate is significantly reduced.
[0099] As can be seen from Examples 3 and Comparative Example 4, if the carbon dots are not subjected to charge adjustment during the preparation of the heat-activated carbon-based nano-antibacterial agent, and the carbon dots are not subjected to heat activation after being compounded with chitosan, the initial antibacterial rate is the lowest, and the antibacterial components are prone to migrate and be lost in large quantities after immersion, and the antibacterial rate is most significantly reduced.
[0100] The above examples are only used to illustrate the technical solutions of the present application, but not limit it; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that they can modify the technical solutions recorded in the foregoing examples, or make equivalent replacement for part of the technical features; and these modifications or replacements will not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A material for antibacterial PET cups, characterized in that it comprises the following raw materials in parts by weight: 85.6-92.7 parts of maleic anhydride grafted and electron beam radiation co-modified PET, 6.3-12.3 parts of thermally activated carbon-based nano antibacterial agent, 1.5-2.3 parts of dispersant, and 0.5-1.3 parts of antioxidant; The maleic anhydride-grafted and electron beam radiation-modified PET is obtained by grafting maleic anhydride onto PET and then subjecting it to electron beam radiation modification. The preparation method of the thermally activated carbon-based nano antibacterial agent is as follows: first, APTES and citric acid are synthesized into carbon dots by hydrothermal method. After the carbon dots are charged and adjusted, they are compounded with chitosan and then thermally activated to prepare the thermally activated carbon-based nano antibacterial agent.
2. The antibacterial PET cup material according to claim 1, characterized in that, The preparation method of the maleic anhydride-grafted and electron beam radiation co-modified PET is as follows: 1) Weigh 85-100 parts of PET, 3-8 parts of maleic anhydride, and 0.1-0.2 parts of initiator, and co-extrude at 250-280 ℃ to obtain maleic anhydride grafted modified PET; 2) Under a nitrogen protective atmosphere, maleic anhydride-grafted modified PET is placed in an electron beam radiation device with a radiation dose of 85-125 kGy, a radiation energy of 5-10 MeV, and a scanning speed of 1-3 m / min.
3. The antibacterial PET cup material according to claim 2, characterized in that, The initiator used is dicumyl peroxide (DCP).
4. The antibacterial PET cup material according to claim 3, characterized in that, The preparation method of the thermally activated carbon-based nano-antibacterial agent is as follows: (1) Add APTES and citric acid to deionized water, stir well, and adjust the pH of the solution to 7-8; (2) Place the mixture in a hydrothermal reactor and react at 185-198 °C for 5-8 h, then cool. (3) The reaction product was filtered with a filter membrane to remove large particulate impurities, and then purified by dialysis with a dialysis bag to obtain a carbon dot solution; (4) Add HCl solution dropwise to the carbon dot solution and adjust the pH to 3-4 while stirring; (5) Weigh chitosan and add it to glacial acetic acid solution to prepare a 0.5-2% acidic chitosan solution; The carbon dot solution was slowly added to the chitosan solution and stirred to react. After centrifugation, the precipitate was collected to obtain the carbon dot / chitosan complex. (6) Thermal activation treatment: The carbon dot / chitosan complex is heated to 135-158 °C at a heating rate of 5-10 °C / min under a nitrogen protective atmosphere and kept at the temperature for 1-2 h for thermal activation treatment. Finally, after grinding, the thermally activated carbon-based nano antibacterial agent is obtained.
5. The antibacterial PET cup material according to claim 4, characterized in that, Step (1) is as follows: Add 0.5-1.5 mL of APTES and 2-5 g of citric acid to 85-105 mL of deionized water, stir for 20-30 minutes, and adjust the pH of the solution to 7-8.
6. The antibacterial PET cup material according to claim 5, characterized in that, Step (3) is as follows: the reaction product is filtered with a 0.22 μm filter membrane to remove large particulate impurities, and then dialyzed with a dialysis bag with a molecular weight cutoff of 1000-3000 Da for 24-38 hours to obtain a carbon dot solution.
7. The antibacterial PET cup material according to claim 6, characterized in that, In step (5), the volume ratio of carbon dot solution to chitosan solution is 1:8-15.
8. The antibacterial PET cup material according to claim 7, characterized in that, In step (5), the carbon dot solution is slowly added to the chitosan solution, stirred at 35-45 ℃ for 2-4 h, centrifuged at 8000-10000 r / min for 5-10 min, and the precipitate is collected to obtain the carbon dot / chitosan complex.
9. The antibacterial PET cup material according to claim 1, characterized in that, The antioxidant used is antioxidant 1010.
10. A method for preparing an antibacterial PET cup material according to any one of claims 1-9, characterized in that, Includes the following steps: (1) First, add maleic anhydride grafted and electron beam radiation co-modified PET and antioxidant into a high-speed mixer and mix at low speed for 5-8 minutes at 60-80℃; (2) Add the thermally activated carbon-based nano antibacterial agent and dispersant, and mix at high speed for 10-15 minutes; (3) After heating and melting extrusion at a temperature of 250-280 ℃, the extrudate is cooled and pelletized to obtain antibacterial PET composite masterbatch.
Citation Information
Patent Citations
A kind of degradable disposable composite plastic water cup and preparation method thereof
CN106832820B
Carbon dot-organic silicon composite fluorescent material as well as preparation method and application thereof
CN114574197A
Cited By
Preparation method of antibacterial multifunctional optical film
CN122011471A